THE INFLUENCE OF WETU TELU ISLAMIC SYNCRETISM ON FIQH LEARNING: A QUALITATIVE CASE STUDY AT MTS BABUL MUJAHIDIN, BAYAN, NORTH LOMBOK - Minarti Indah; Yulia Oktarina; Muhammad Fadly Habibi; Eldo Delamontano (Edukasi Islami : Jurnal Pendidikan Islam, 2026)
This study examines the effects of the Islamic Wetu Telu syncretism on Fiqh education at the Madrasah Tsanawiyah Babul Mujahidin, which is situated in the Traditional Village of Bayan in North Lombok. The teaching of Fiqh in the madrasah does not occur in a socially neutral environment; it is shaped by the local cultural and religious practices. The aim of this research is to explore how these local values influence students' understanding and attitudes towards religion. A qualitative case study method was employed for this purpose. Data was gathered through observation, in-depth interviews with five teachers and thirty students, as well as an analysis of educational documents. Data analysis was conducted in both descriptive and analytical ways, focusing on the interaction between local religious practices and Fiqh education. Findings indicate that the syncretism of Islamic Wetu Telu significantly impacts students' comprehension of Fiqh, especially regarding ritual worship. Approximately 68% of students reported challenges in grasping worship practices due to discrepancies between family traditions and normative Fiqh teachings, while 57% of teachers observed that students tended to follow the guidance of traditional leaders more than formal instructions. Despite these obstacles, local values such as community cohesion, respect for traditional authority, and social balance serve as positive social capital when applied through a contextual and dialogical teaching approach. The study concludes that the Islamic Wetu Telu syncretism does not necessarily impede formal Islamic education; rather, it can act as an educational bridge if managed in a contextual and dialogical manner. These findings underscore the significance of cultural sensitivity in developing Fiqh instruction within local communities.